Who Pays for Justice? Perspectives on State Court System Financing and Governance - McGovern, Geoffrey (RAND Corporation, 2014)
RAND Corporation researchers surveyed experts from five states that use a variety of approaches to funding state court systems to assess financing, accounting, and governance issues under various systems